2006
DOI: 10.1523/jneurosci.0651-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin-Dependent  -Secretase-Mediated Control of p53-Associated Cell Death in Alzheimer's Disease

Abstract: Presenilins (PSs) are part of the ␥-secretase complex that produces the amyloid ␤-peptide (A␤) from its precursor [␤-amyloid precursor protein (␤APP)]. Mutations in PS that cause familial Alzheimer's disease (FAD) increase A␤ production and trigger p53-dependent cell death. We demonstrate that PS deficiency, catalytically inactive PS mutants, ␥-secretase inhibitors, and ␤APP or amyloid precursor protein-like protein 2 (APLP2) depletion all reduce the expression and activity of p53 and lower the transactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
154
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(166 citation statements)
references
References 63 publications
11
154
1
Order By: Relevance
“…We have examined the ability of p53 to modulate PrP c promoter transactivation and mRNA expression and we show that p53 acts as a transcriptional activator of PrP c by binding directly to the suspected promoter sequence. Furthermore, we previously established that the ␤-amyloid precursor protein (␤APP-intracellular domain amyloid intracellular domain (AICD) generated after presenilin-dependent ␥-secretasemediated cleavage of ␤APP behaves as a transcriptional activator of p53 (Alves da Costa et al, 2006). Here, we show that presenilins also control PrP c transcription in a presenilin-dependent manner by increasing AICD-induced p53 expression.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…We have examined the ability of p53 to modulate PrP c promoter transactivation and mRNA expression and we show that p53 acts as a transcriptional activator of PrP c by binding directly to the suspected promoter sequence. Furthermore, we previously established that the ␤-amyloid precursor protein (␤APP-intracellular domain amyloid intracellular domain (AICD) generated after presenilin-dependent ␥-secretasemediated cleavage of ␤APP behaves as a transcriptional activator of p53 (Alves da Costa et al, 2006). Here, we show that presenilins also control PrP c transcription in a presenilin-dependent manner by increasing AICD-induced p53 expression.…”
Section: Introductionmentioning
confidence: 74%
“…We have previously demonstrated that AICDs can positively control p53 at the transcriptional level (Alves da Costa et al, 2006). In silico examination of the PrP c promoter revealed a putative although incomplete p53-binding site (el-Deiry et al, 1992) (Fig.…”
Section: Aicd-mediated Regulation Of Prpmentioning
confidence: 93%
“…In TIF-IA mutants, one of the earliest events triggered by nucleolar damage is the increased stabilization of the transcription factor p53, and we show that inhibition of p53 abrogated the cellular loss. Interestingly, the importance of p53 for neurodegeneration has been shown in Huntington's, Alzheimer's, and Parkinson's diseases (Bae et al, 2005;Alves da Costa et al, 2006;Nair et al, 2006). The question remains how p53 can relay its devastating function in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of an excess amount of Aβ activates p53 and induces neurodegeneration [18]. p53-associated cell death in Alzheimer disease was dependent on presenilin [34]. However, on the other hand, overexpression of Aph-1 and Pen-2 reduced p53 expression and activity and suppressed apoptosis [35], and consistently, knockdown of Pen-2 resulted in p53-dependent apoptosis [36].…”
Section: Discussionmentioning
confidence: 99%